Essential role of microglia in the fast antidepressant action of ketamine and hypidone hydrochloride (YL-0919) - Chang, Hai-Xia; Dai, Wei; Bao, Jin-Hao; Li, Jin-Feng; Zhang, Ji-Guo; Li, Yun-Feng (Frontiers in Pharmacology, 2023)
Intracerebral microglia play a vital role in mediating central immune response, neuronal repair and synaptic pruning, but its precise role and mechanism in fast action of antidepressants have remained unknown. In this study, we identified that the microglia contributed to the rapid action of antidepressants ketamine and YL-0919. The depletion of microglia was achieved with the diet containing the colony-stimulating factor 1 receptor (CSF1R) inhibitor PLX5622 in mice. The tail suspension test (TST), forced swimming test (FST) and novelty suppressed feeding test (NSFT) were employed to evaluate the rapid acting antidepressant behavioral of ketamine and YL-0919 in the microglia depletion model. The number of microglia in the prefrontal cortex (PFC) was assayed by the immunofluorescence staining. The expressions of synaptic proteins (synapsin-1, PSD-95, GluA1) and brain-derived neurotrophic factor (BDNF) in the PFC were tested by Western blot. The results indicated that the immobility duration in FST and the latency to feed in NSFT were shortened 24 h after an intraperitoneal (i.p.) injection of ketamine (10 mg/kg). The microglial depletion of PLX3397 blocked the rapid antidepressant-like effect of ketamine in mice. In addition, the immobility time in TST and FST as well as latency to feed in NSFT were reduced 24 h after the intragastric (i.g.) administration of YL-0919 (2.5 mg/kg), and the rapid antidepressant effect of YL-0919 was also blocked by the microglial depletion using PLX5622. About 92% of microglia in the prefrontal cortex was depleted in PLX5622 diet-fed mice, while both ketamine and YL-0919 promoted proliferation on the remaining microglia. YL-0919 significantly increased the protein expressions of synapsin-1, PSD-95, GluA1 and BDNF in the PFC, all of which could be blocked by PLX5622. These results suggested the microglia underlying the rapid antidepressant-like effect of ketamine and YL-0919, and microglia would likely constitute in the rapid enhancing impact of synaptic plasticity in the prefrontal cortex by YL-0919.